Infection with toxigenic and atoxigenic strains of Aspergillus flavus induces different transcriptional signatures in maize kernels. Issue 1 (1st January 2017) - Lanubile, Alessandra; Maschietto, Valentina; Battilani, Paola; Marocco, Adriano
ABSTRACT: The application of atoxigenic Aspergillus flavus strains in maize fields has been shown to be an effective strategy for controlling contamination of aflatoxins, potent carcinogens produced by the fungus. This study monitored the expression levels of 18 defense genes against toxigenic and atoxigenic A. flavus strains in developing maize kernels over a time course of 96 h after inoculation. A stronger upregulation of genes encoding pathogenesis-related proteins, oxidative stress-related proteins, transcriptional factors and lipoxygenases were observed in response to the atoxigenic strain. On the other side, this strain showed a significant enhanced growth in the later stages of infection, measured as copy number of the constitutive calmodulin gene. These results suggest that overexpression of maize-defense-associated genes observed in response to the atoxigenic strain could contribute to an aflatoxin reduction. The identification of genes significantly affecting the resistance to A. flavus or aflatoxin accumulation would accelerate the development of resistant cultivars.